STRENGTHENING FINANCIAL SECURITY AS AN IMPERATIVE IN THE ENTERPRISE FINANCIAL REHABILITATION MANAGEMENT SYSTEM - KHOMA, Dmitriy; LOPATOVSKA, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The purpose of the article is to substantiate the priorities, tools and means of strengthening the financial security of the enterprise in the management system of its financial rehabilitation. The study emphasizes the relevance of the link between the policy of financial security and management of financial rehabilitation of the enterprise. The author's approach to the formation of methods of integrated analysis of the level of financial security of the entity is presented. The integral values of financial security of the enterprise are calculated and its temporal graphic interpretation is given. The forecast of the level of financial security of the enterprise is made. The strategic guidelines of the policy of improving the financial security of the enterprise in the management system of its financial rehabilitation have been determined. The purpose of the policy of strengthening the financial security of the enterprise is substantiated. The strategic goals of the policy of management and ensuring sustainable financial security of the enterprise are determined. The scientific novelty of the research results is the development of a policy that allows to link the provision of sustainable financial security and quality management of the process of financial rehabilitation of business in a deep crisis.The applied significance of the research results is to summarize the main measures (tools) to be implemented by the company to ensure its financial security and successful financial rehabilitation in the deep financial and economic crisis in Ukraine, namely - improving quality and competitiveness of products; improving the structure of the balance sheet; constant planning and monitoring of deviations of the actual amount of income from the estimated critical volumes of the enterprise; initiating the practice of forming a reserve and insurance fund by allocating a certain percentage of net profit for these purposes; constant planning and monitoring of financial stability and liquidity indicators; planning, design and gradual modernization of production facilities; creation of the department of financial risk management and rehabilitation and the beginning of the practice of risk forecasting in all areas of activity.
Keywords: enterprise management; financial rehabilitation; financial security; financial management; priorities of sustainable development of the enterprise